AMINO ACID PROFILE OF JELAWAT FISH (Leptobarbus hoevenii) BASED ON THE DIFFERENCE OF HARVESTING TIME - Abrar, Muhammad Zaid; ', Edison; ', Sumarto (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research aims to know the amino acid profile of jelawat fish based onthe difference of harvest time. Jelawat fish samples divided into three age groups,they are 6, 10 and 14 months old. The fish samples then analyzed the amino acids,proximate levels (water, fat, protein, and ash), water soluble protein (PLA) andsalt soluble protein (PLG). Research’s result from jelawat fish at 6,10 and 14months old has a number of consecutive amino acids 22.91%, 21.59%, 18.78;water content 68.93%, 66.81%, 66.23%; fat content 6.12%, 8.31%, 10.73%;protein content 23.03%, 23.56%, 20.91%; ash content 1.52%, 1.23%, 1.14%; PLAcontent 1.64%, 3.35%, 2.65% and PLG content 2.73%, 3.80%, 3.40%. Theconclusion of this research was jelawat fish at the age of harvest time 6-10 monthsold had the most optimal amino acids and protein content.Keywords: Fish jelawat, harvesting time, amino acids